Preparation of Bacillus subtilis cell samples and generation of an SDS-PAGE - Thu TM Dao; Dat D Truong; Lan NH Duong; Nhi NY Nguyen; Hoang D Nguyen (BioTechniques, 2023)
Bacillus subtilis is a critical host for producing recombinant proteins. However, the SDS-PAGE process, including the sample preparation steps, varies among B. subtilis-related studies, making it impossible to compare findings. Hence, this paper provides a simple guide to culture and collect B. subtilis cells through an OD600 measurement and a protocol for SDS-PAGE. These techniques were applied to check the expression of a BgaB, a reporter protein and LukF-PV, a potential vaccine candidate against S. aureus, in the cytoplasm of B. subtilis under the control of a strong promoter, Pgrac212. This protocol could be helpful for scientists in preparing samples and generating an SDS-PAGE experiment, as well as favoring the unification of research about protein expression in B. subtilis.